Evaluation of a tool to improve the quality of preceptor written feedback for family medicine residents: training and use of a CanMEDS-MF competency-based criterion guide - Desjardins, Chloé; Pitre, Lyne; Adjo, David; Sagne, Jean Henri; Fotsing, Salomon; Dionne , Éric; Seale, Edward; Pomerleau, Marjorie; Philippe, Marissa; Gharib, Georges; et al. (Canadian Medical Education Journal, 2023)
Background: Written feedback is essential in resident teaching, but preceptors are not always well equipped to provide relevant feedback. The purpose of this study was to evaluate the effectiveness of multi-episodic training and the use of a criterion-referenced guide for written feedback for family medicine preceptors in a French-language academic hospital. Method: Twenty-three (23) preceptors participated in the training and used the criterion-referenced guide to guide them during the written evaluation in an evaluation sheet named "Field Notes". The content of these Field Notes was analyzed according to completion, the rate of specific feedback, and the rate of feedback by CanMEDS-MF role before and after the training over a 3-month period. Results: Based on the analysis of the Field Notes (n=70 pre-test; n=138 post-test), an increase in the percentage of completion (50% vs. 92%, z=2.97, p=0.0030) and specific feedback (59% vs. 92%, z=2.47, p=0.0137) was noted. There was no significant increase in feedback by CanMEDS-MF role. Conclusions: The development of multi-episodic training and a criterion-referenced guide, created according to the CanMEDS-MF repository, suggests an improvement in comprehensive and specific written feedback in family medicine education.